POTENSI DESA DAN STRATEGI PENERAPAN EKONOMI ISLAM DALAM PENGELOLAAN BISNIS BUMDES - Muhammad Ash-Shiddiqy (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
This research departs from the not yet optimal role of the BUMDes institution as a village business driver that carries a social mission and commercial mission in the three villages that are the objects of this research, namely Rompo Village, Karumbu Village and Rupe Village. From this, the two main problems to be answered are what is the potential that can be managed for the development of BUMDes business units and how is the strategy for implementing Islamic economics (sharia) in managing BUMDes business. To answer these problems, the researcher uses two analyzes as a theoretical framework, village potential analysis, and SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results of the research analysis are the potential business sectors that deserve to be developed are businesses in the real sector (agriculture, livestock and fisheries), trade, tourism, and agro-industry sectors. While the results of the SWOT analysis recommend (a) S-O Strategy; The BUMDes Business management approach uses Islamic principles with a business unit management strategy based on the real sector and business units of Islamic microfinance institutions. (b) W-O Strategy, HR development strategy and entrepreneurship (c) S-T Strategy, Islamic economic implementation strategy. (d) W-T Strategy; Build awareness and motivation to work and be alliance with Islamic concepts, Instill values ​​of concern for local village products, Increase participation of business actors and Develop several business lines